Changes in the eye contour signs due to age among Mexican women: Comparison with women of other ethnic origins. (5th November 2020) - Flament, F.; Coubard, O.; Cruz, R.; Flores, F.
Abstract: Objective: To evaluate the changes in certain ocular signs because of age, among Mexican women and to compare these with those previously obtained on women of other ethnicities. Material and methods: Photographs were taken of the faces of 203 Mexican women of different ages, under standardized conditions. These photographs allowed us to focus and define nine ocular signs, which were then graded by 15 experts and dermatologists, using standardized scales provided by a reference Skin Aging Atlas. Hence, the same protocol, previously used on 3240 women of four other ethnic origins (Caucasian: 600; Chinese: 990; Japanese: 1010; Indian: 300; African: 340), allowed us to compare the results obtained on Mexican women. Results: The severity of crow's feet wrinkles for Mexican women shows a more intense progression with age than those of women from other ancestries. The lower eyelid wrinkles of Mexican women, that show weak or erratic changes with time, were however found to have higher and significant severity at a young age. Pigmentation disorders of their ocular area were found less pronounced as compared to those of Asian or Indian women. Eye bags were observed with similar slight changes in all five ancestries. Conclusion: The present work confirms that the clinical signs of age for the female eye area develop differently depending on the ethnic origins of the volunteer. Abstract : Changes in four ocular wrinkles signs of Mexican women, with age. Résumé: Objectif: D'évaluer les variations avec l'âge de signes cliniques de la zone des yeux pour des femmes mexicaines et de les comparer avec des données précédemment acquises pour des femmes d'autres origines ethniques. Materiel et Methodes: 203 femmes mexicaines, d'âges différents, ont été photographiées sous des conditions standardisées pour analyser neuf signes cliniques relatifs à la zone des yeux. Ces derniers couvrent des clusters cliniques de Rides/Texture, de Désordres pigmentaires ou de Ptose/relâchement et ont été évalués dans leurs sévérités respectives suivant les échelles éditées dans les Atlas cliniques du Vieillissement de référence par un groupe de 15experts et dermatologues. Ce même protocole a été utilisé précédemment sur 3240 femmes de 4 origines différentes (caucasiennes :600 ; chinoises : 990 ; japonaises : 1010 ; indiennes : 300 ; africaines : 340) et nous permet de pouvoir comparer ces résultats aux données obtenues sur les femmes mexicaines. Resultats: La sévérité des rides de la patte d'oie pour les femmes mexicaines présente une progression plus rapide avec l'âge que celles observées dans les autres ethnicités. Les rides de la paupière inférieure des femmes mexicaines, présentant des variations faibles ou erratiques avec l'âge, ont cependant été scorées avec une sévérité significativement supérieure pour les âges les plus jeunes. Les désordres pigmentaires pour la zone des yeux ont été trouvés comme moins prononcés en comparaison des femmes d'origine asiatique ou indienne. Les poches sous les yeux ont été observées avec des évolutions similaires avec l'âge quelle que soit l'origine ethnique. Conclusion: Ces travaux confirment que les signes cliniques de la zone des yeux présentent différentes évolutions avec l'âge en fonction des origines ethniques